Economic and socio-cultural drivers of necessity and opportunity entrepreneurship depending on the business cycle phase - Martínez-Rodriguez, Isabel; Callejas-Albiñana, Fernando E.; Callejas-Albiñana, Ana Isabel (Journal of Business Economics and Management, 2020)
This paper offers an in-depth examination of the behavior of necessity- and opportunitydriven entrepreneurship. First, it considers their relevance to total entrepreneurial activity. It then seeks to determine which socio-cultural and economic factors affect the two types of entrepreneurship, as well as their relative importance for a sample of 32 previously selected countries during a period of expansion (2001–2008) and of crisis and recovery (2009–2016). The analyzed factors include monetary and fiscal policy instruments (economic factors) and representative variables of governance and human capital (socio-cultural ones). The findings show that both necessity- and opportunity-driven entrepreneurship largely explain the behavior of total entrepreneurial activity. They moreover show that the explanatory factors of both kinds of entrepreneurship differ depending on the business cycle phase considered. These findings will be key to proposing efficient economic policy measures to promote entrepreneurial activity and, thus, economic growth in different economies around the world.